(untitled) (Indian Journal of Fibre & Textile Research (IJFTR), 2025)
In this study, a new type of elastomeric fibre based on elastomeric polyester, i.e., poly (butylene terephthalate)-block-(tetramethylene oxide) is used as poly (ether-ester)1, and poly (ether-ester)2 obtained by melt spinning poly (ether-ester)1 with poly (butylene terephthalate). These elastomeric staple fibres are then spun into elastomeric yarns using ring and compact spinning systems. The spun yarns exhibit varying levels of elastic recovery at different fixed elongation levels, depending on the blend ratio. Additionally, filament yarns, including partially oriented yarn, fully drawn yarn and poly (ether-ester) polyester-based filament yarns, are tested using the same fixed extensions for comparison. The elastic recovery obtained is greater than 95% in nearly all cases, meeting the acceptable level for elastomeric yarn production. Other important functional elastic recovery parameters, such as permanent set, immediate elastic recovery, and delayed elastic recovery, are also determined. This study confirms that these elastomeric yarns offer a promising new material for the textile and fashion markets.